2012
DOI: 10.1016/j.toxlet.2012.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Anti-aging effects of deuterium depletion on Mn-induced toxicity in a C. elegans model

Abstract: Work with sub-natural levels of deuterium (D) in animals has demonstrated an anti-cancer effect of low D-concentration in water. Our objective was to investigate whether deuterium-depleted water (DDW) can overturn reverse manganese (Mn)-induced reduction in life span, using the Caenorhabditis elegans (C. elegans) as a model system. DDW per se had no effect on worm’s life span 48 h after treatment; however, it reversed the Mn-induced decrease in C. elegans life span. Mn reduced DAF-16 levels, a transcription fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 34 publications
1
43
0
Order By: Relevance
“…Forth way is to target hydrogen bond network of cancer signaling by the proton beam radiation disrupting a hydrogen bond network and causing apoptosis of cancer cells. However, robustness and stability of the cancer system could be targeted by the simultaneous targeting of the redox balance change [Radisavljevic, 2008] and hydrogen balance change [Somlyai et al, 2010;Tong et al, 2011;Avila et al, 2012; Guitart et al, 2017], or proton beam radiation [Marshall et al, 2016] and/or with nitric oxide balance change [Radisavljevic, 2003] all leading to apoptosis of the cancer cells, but in this case there is always a risk for failure of the entire living system too, instead of rather slow then fast apoptosis of cancer cells by slow conversion of the positive feedback loops and slow disappearance of cancer malignant phenotype [Radisavljevic, 2003[Radisavljevic, , 2004a[Radisavljevic, ,b, 2008[Radisavljevic, , 2013a[Radisavljevic, ,b,c, 2015a[Radisavljevic, ,b, 2016. …”
mentioning
confidence: 99%
“…Forth way is to target hydrogen bond network of cancer signaling by the proton beam radiation disrupting a hydrogen bond network and causing apoptosis of cancer cells. However, robustness and stability of the cancer system could be targeted by the simultaneous targeting of the redox balance change [Radisavljevic, 2008] and hydrogen balance change [Somlyai et al, 2010;Tong et al, 2011;Avila et al, 2012; Guitart et al, 2017], or proton beam radiation [Marshall et al, 2016] and/or with nitric oxide balance change [Radisavljevic, 2003] all leading to apoptosis of the cancer cells, but in this case there is always a risk for failure of the entire living system too, instead of rather slow then fast apoptosis of cancer cells by slow conversion of the positive feedback loops and slow disappearance of cancer malignant phenotype [Radisavljevic, 2003[Radisavljevic, , 2004a[Radisavljevic, ,b, 2008[Radisavljevic, , 2013a[Radisavljevic, ,b,c, 2015a[Radisavljevic, ,b, 2016. …”
mentioning
confidence: 99%
“…Both effects are highly reproducible in C. elegans. Increased expression of Akt was also observed in worms exposed to Mn (Avila et al 2012b). …”
Section: Introductionmentioning
confidence: 91%
“…It was also noted the positive impact of DDW on indicators of saturation the liver tissue by oxygen: the observed increase in pO 2 was ∼15%, i.e., cell respiration increased 1,3 times [38]. On beneficial effect on health of experimental mice evidenced the increased resistance and weight increase compared with the control group [39]. It was also indicated that DDW increases the rate of metabolic reactions.…”
Section: Clinical Evidence On the Benefits Of Deuterium Depleted Watementioning
confidence: 99%